Plato's Timaeus and the biblical creation accounts: cosmic monotheism and terrestrial polytheism in the primordial history - Gmirkin, Russell E. (Copenhagen international seminar, 2022)
Comparative methodology and Genesis 1-11 -- Genesis 1 and creation myths -- Genesis 1 and Greek cosmogonies -- Genesis 1 as philosophy -- Genesis 1 as science -- Genesis 2-3 as myth -- Genesis 2-11 and Plato's Critias -- Cosmic monotheism and terrestrial polytheism in Plato and the Bible.